Design, synthesis and evaluation of imidazo[1,2-a]pyrazin-8(7H)-one derivatives as acetylcholinesterase inhibitors and antioxidants - Du, Wen-Rong; Wei, Ben-Ben; Guo, Xin-Yuan; Lan, Yong; Shang, Pan-Pan; Wang, Yi-Xuan; Zhou, Xue-Wei; Wang, Xiao-Ke; Ma, Zheng-Yue (Medicinal chemistry research, 2024)
A series of 8-(piperazin-1-yl)imidazo[ 1,2-a ]pyrazine derivatives were designed and synthesized as acetylcholinesterase inhibitors (AChEIs) and antioxidants for the treatment of Alzheimer’s disease (AD). Moreover, the biological evaluation results demonstrated that these synthesized compounds exhibited moderate inhibitory activities toward acetylcholinesterase (AChE) and radical scavenging activities. Among them, compound 17r was the most potent AChE inhibitor with an IC 50 value of 0.47 μM and moderate inhibitory activity against butyrylcholinesterase (BuChE) (IC 50 = 11.02 μM). The selectivity index (SI) value of AChE over BuChE was 23.45, surpassing that of the reference drug galantamine (AChE IC 50 = 5.01 μM, BuChE IC 50 = 18.46 μM, SI = 3.68). Compound 17o had the best antioxidant activity with an IC 50 value of 89.33 μM, which was lower than that of ascorbic acid (IC 50 value = 25.70 μM) as the control drug. Furthermore, the results of molecular docking studies indicated that 17r could simultaneously bind to both catalytic active site and peripheral anionic site of AChE, which was consistent with the mixed inhibition pattern shown by enzyme kinetic studies. The interaction’s stability of 17r -AChE/BuChE were also assessed using a conventional atomistic 100 ns dynamics simulation study, which revealed the conformational stability of representative compound 17r in the cavity of the AChE. In addition, the molecular properties of all compounds were predicted online through the SwissADME, and the best active compound 17r matched the properties of most orally administered drugs. Based on the biological activity and molecular properties, compound 17r as AChEI was valuable for further development.